Search for heavy neutron clusters in nuclear fission; Bulletin of the Russian Academy of Sciences: Physics; Vol. 73, iss. 2 - Varlachev V. A. Valery Aleksandrovich; Garapatski A. A. Alexander Alexandrovich; Dudkin G. N. Gennadiy Nikolaevich; Padalko V. N. Vladimir Nikolaevich; Skuridin V. S. Viktor Sergeyevich; Солодовников Е. С. Евгений Семёнович; Chibisov E. V. Evgeny Vladimirovich (2009, 2009)
Title screen